N - acetyltransferases required for iron uptake and aminoglycoside resistance promote virulence lipid production in Mycobacterium marinum - Bradley S. Jones; Vikram Pareek; Daniel D. Hu; Simon D. Weaver; Camille Syska; Grace Galfano; Matthew M. Champion; Patricia A. Champion (Proceedings of the National Academy of Sciences, 2025)
Phagosomal lysis is essential for mycobacterial infection of macrophages. Acetylation is a protein modification mediated enzymatically by N-acetyltransferases (NATs) that impacts bacterial pathogenesis and physiology. To identify NATs required for lytic activity, we leveraged Mycobacterium marinum, a nontubercular pathogen and a model for Mycobacterium tuberculosis. M. marinum hemolysis is a proxy for phagolytic activity. We generated M. marinum strains with deletions in conserved NAT genes and screened for hemolytic activity. Several conserved lysine acetyltransferases (KATs) contributed to hemolysis, which is mediated by the ESX-1 secretion system and by the virulence lipid phthiocerol dimycocerosate (PDIM). Using thin-layer chromatography, we found that MbtK, a conserved acyl-transferase required for mycobactin siderophore synthesis and virulence, was required for PDIM and phenolic glycolipid (PGL) production. Exogenous addition of sodium propionate or Mycobactin J restored PDIM/PGL production in the Δ mbtK strain. The Δ mbtK M. marinum strain was attenuated in macrophage and Galleria mellonella infection models. Constitutive expression of either eis or papA5, which encode a KAT required for aminoglycoside resistance and a PDIM/PGL biosynthetic enzyme, rescued PDIM/PGL production, and virulence of the ∆ mbtK strain. Eis N-terminally acetylated PapA5 in vitro, providing a plausible mechanism for restored lipid production. Overall, our study establishes connections between the MbtK and Eis NATs, and between iron uptake and PDIM and PGL synthesis in M. marinum . Our findings underscore the multifunctional nature of mycobacterial NATs and their connection to key virulence pathways.